Response of Onion (Allium cepa L.) Cultivars to Nitrogen and Potas1sium Fertilization under Semi-arid Conditions. - Yadav, R L; Sen, N L; Yadav, B L; dhaka, R S (Annals of Arid Zone, 2016)
Short Communication